The effects of anthropogenic noise and human activities on ungulate behavior - Brown, Casey Lynn, author; Angeloni, Lisa M., advisor; Crooks, Kevin R., advisor; Fristrup, Kurt Murray, committee member (Colorado State University. Libraries, 2010)
The effect of anthropogenic noise on terrestrial wildlife is a relatively new area of study with broad ranging management implications. Human activities may increase noise in protected areas, including U.S. National Parks. Grand Teton National Park (GTNP) draws nearly 4 million visitors a year to recreate on park roads, trails, and campgrounds. As visitors travel through the park and congregate around wildlife viewing locations, noise is one of the many disturbance stimuli introduced into the environment. This study investigated the potential impacts of human induced noise and human activities on the behavior of elk (Cervus elaphus) and pronghorn (Antilocapra Americana) along a transportation corridor in GTNP. We conducted roadside scan surveys and focal observations of ungulate behavior while concurrently recording human activity and anthropogenic noise. Ungulates were less responsive (less likely to perform vigilant, flight and defensive behaviors) in noisy environments when more vehicles were passing and more responsive when pedestrians were present. These effects of noise on responsive behavior may have both positive and negative implications for wildlife conservation and management.
Keywords: ungulate; road; noise; behavior; conservation; acoustic; Ungulates -- Effect of noise on; Ungulates -- Wyoming -- Grand Teton National Park; Ungulates -- Ecology; Noise -- Physiological effect; Human-animal relationships